2017
DOI: 10.1111/micc.12388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sympathetic nerve blockade on low‐frequency oscillations of forearm and leg skin blood flow in healthy humans

Abstract: Our data support that the frequency band (0.021-0.052 Hz) associated with neurogenic activity appears to be correct having a large sympathetic component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Additionally, wavelet analysis may be unable to delineate local and reflex sympathetic activity. While previous work has clearly demonstrated that the neural frequency band (0.02-0.05 Hz) is mostly sympathetic (Hodges et al 2017a), there is also likely to be some sensory nerve involvement. Thus, categorical statement of what the neural influences are and whether the observed effects are of local or reflex origin on cutaneous vascular control are not possible at the present time with this approach.…”
Section: Limitationsmentioning
confidence: 82%
See 4 more Smart Citations
“…Additionally, wavelet analysis may be unable to delineate local and reflex sympathetic activity. While previous work has clearly demonstrated that the neural frequency band (0.02-0.05 Hz) is mostly sympathetic (Hodges et al 2017a), there is also likely to be some sensory nerve involvement. Thus, categorical statement of what the neural influences are and whether the observed effects are of local or reflex origin on cutaneous vascular control are not possible at the present time with this approach.…”
Section: Limitationsmentioning
confidence: 82%
“…This method characterizes the dynamics of signals over a wide frequency D r a f t range, from 0.005 to 1.6 Hz. The six frequency intervals and associated physiological functions were as follows: 0.005-0.01 Hz (endothelial: NO-independent) and 0.01-0.02 Hz (endothelial: NO-dependent) (Kvandal et al 2006); 0.02-0.05 Hz (neurogenic) (Söderström et al 2003, Hodges et al 2017a; 0.05-0.15 Hz (myogenic) (Johnson 1989, Söderström et al 2003; 0.15-0.40 Hz (respiratory); 0.40-1.6 Hz (cardiac).…”
Section: Wavelet Transformmentioning
confidence: 99%
See 3 more Smart Citations